MANAJEMEN PRIVASI KOMUNIKASI GAY DALAM HUBUNGAN INTERPERSONAL - Wiragana, Biladi Muhammad; Melita, Yerah (Jurnal Insani, 2023)
The background of this research is that people's thinking has begun to open up regarding the livelihoods of communities that have different sexual orientations, especially among the younger generation, but on the other hand there is still discrimination by law enforcement officials and social law by the community. This study focuses on gay privacy management in interpersonal relationships. This study aims to determine the privacy management of gay communication in interpersonal relationships. The theory used in this research is communication privacy management theory. While the method used by using a qualitative approach is descriptive qualitative. This method is used to search for, obtain data, and compile and interpret data that has been obtained from informants. By taking purposive sampling. Data collection techniques used are observation, interviews and documentation. Technical data validity using source and method triangulation. The results of the study show that gays are very protective of information about their sexual orientation even with family and close friends. Gays are more likely to close their sexual orientation meetings and only open up to other gays. Some gay informants have introverted, ambiverted, and extroverted characteristics in their social environment, but are still reluctant to provide private information. Private information for some informants is more comfortable with keeping their gay information from the surrounding environment, because the community itself still does not accept the existence of the gay community in society. One of the informants stated that being gay is a disgrace and a disease in society, so he was reluctant to disclose this information. He prefers to ask God for guidance and asks his mother to pray so that he will be better. Informants hope that society can provide space and respect those with different sexual orientations.